2019
DOI: 10.3390/md17020132
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Extraction from Nannochloropsis gaditana Using Carbon Dioxide at Supercritical Conditions

Abstract: This research shows that carbon dioxide supercritical fluid (CO2-SF) is an emerging technology for the extraction of high interest compounds for applications in the manufacturing of pharmaceuticals, nutraceuticals, and cosmetics from microalgae. The purpose of this study is to recover fatty acids (FAs) and, more precisely, eicosapentaenoic acid (EPA) from Nannochloropsis gaditana biomass by CO2-SF extraction. In the paper, the effect of mechanical pre-treatment was evaluated with the aim of increasing FAs reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Matrix solid-phase dispersion (MSPD) of microalgae biomass was carried out using a ball miller to enhance the extraction efficiency of intracellular compounds [19,24,27]. Therefore, the pretreatment conditions were optimized to enhance the recovery of lutein from S. almeriensis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Matrix solid-phase dispersion (MSPD) of microalgae biomass was carried out using a ball miller to enhance the extraction efficiency of intracellular compounds [19,24,27]. Therefore, the pretreatment conditions were optimized to enhance the recovery of lutein from S. almeriensis .…”
Section: Resultsmentioning
confidence: 99%
“…The optimum stirring rate provides the effective mechanical force, which leads to homogenously break the microalgae cell. Therefore, the degree of MSPD needs to be optimized for each microalga due to their varied chemical composition of intracellular molecules and the cell wall structure of microalgae biomass [24,26]. In the second step, the pre-treatment time (2.5–10 min) was optimized to enhance the lutein recovery at 400 rpm with 0.4 DE/biomass ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data showed that the maximum recovery of astaxanthin and lutein could be achieved at low temperature and high pressure (50 °C and 550 bar, respectively) adopting the lowest investigated CO 2 flow rate (3.62 g/min), while a higher flow rate (14.48 g/min) increased astaxanthin and lutein purities. Molino et al [20] studied the effect of extraction pressure (250, 400 and 550 bars) and temperature (50 and 65 °C) at CO 2 flow rates of 7.24 and 14.48 g/min for EPA recovery from Nannochloropsis gaditana biomass during SF-CO 2 extraction, resulting in a maximum EPA recovery of 27.4% at 65 °C and 250 bars with a CO 2 flow rate of 7.24 g/min.…”
Section: Resultsmentioning
confidence: 99%
“…The flow rate of CO 2 defines the residence time for the contact between the solute and the solvent, which have various effects on the selectivity of bioactive compounds and extraction efficiency. To the best of authors’ knowledge, only a few reports in the literature on the role of CO 2 flow rate on the selectivity of bioactive compounds and extraction efficiency exist [16,17,20,21,22]. Machmudah et al [22] investigated the effect of CO 2 flow rate (2–4 mL/min) at 50 MPa and 50 °C for astaxanthin recovery from H. pluvialis , and they found that the amount of total extract could be increased, whereas the amount of astaxanthin in the extract almost remained unchanged.…”
Section: Introductionmentioning
confidence: 99%